Policies for high quality, safe, and sustainable food supply in the Greater Mekong Subregion. - Weaver, Thomas R.D (Asian Development Bank, 2019)
It also explores the actions and policy options that could be pursued. Three themes are examined: (i) improving food safety and quality; (ii) inclusive and sustainable, safe and environment friendly agriculture products; and (iii) value chains for safe and environment friendly agriculture products. This aligns with the ASEAN Economic Community blueprint, which calls for the creation of a single market and production base for food, agriculture, forestry; and integration of the region into the global economy.